Changes of drive to recovery ratio during 2000m ergometer rowing among junior national rowers - Muhammad Aiman, U.; Zainuddin, F. L.; Razman, R. M.; Shaharudin, S. (Malaysian Journal of Movement, Health and Exercise, 2019)
Rowing has two stroke phases: the drive phase and recovery phase. The objective of our study was to evaluate the changes of drive to recovery ratio during rowing on a dynamic ergometer. Ten male national junior rowers participated in the study. Three-dimensional motion was recorded using nine infrared cameras. Rowing motions were captured in ten strokes for every 500m section of 2000m rowing time trial on a dynamic ergometer. Two-way ANOVA was performed to compare the duration of drive and recovery phases across 500m sections of 2000m time trial. The findings showed that there were no significant interactions between drive and recovery phases and distance covered. However, there was significant interaction between the duration of the recovery phase and distance covered. Participants were consistent in maintaining the duration of drive and recovery phase at 500m, 1000m, and 1500m; in the final 500m section, the rowers sprinted as fast as possible with high stroke rates. Drive to recovery ratio across 2000m dynamic ergometer rowing was 1:1. From the study, the strategy to minimise time to completion may be managed by adjusting the time spent during drive and recovery phases in each section of the 2000m time trial. Crew pairings can be conducted according to personal drive to recovery ratio to enhance rowing synchronisation.